RANCANG BANGUN ALAT BLANKET WARMER PADA PASIEN HIPOTERMIA BERBASIS INTERNET OF MEDICAL THING - Rizki Ramadhani (Institut Kesehatan dan Teknologi Al Insyirah, 2024)
This research aims to design and build a blanket warmer device that can be used for patients suffering from hypothermia, with the integration of Internet of Medical Things (IoMT) technology. Hypothermia is a serious medical condition that can be life-threatening if not addressed quickly and appropriately. The device designed in this study is expected to provide an effective solution to the problem of hypothermia by utilizing the latest technology. The method used in this research is the prototyping method, which allows for system development through the creation of a physical model as an initial version. The research process includes data collection, literature study, and system design that encompasses block diagrams and flowcharts. The result of this research is a blanket warmer device that can automatically monitor and regulate temperature, as well as connect with other devices via IoMT, thereby facilitating medical personnel in monitoring patient conditions. It is hoped that this device can improve the quality of patient care and provide a positive contribution to the field of health.